Viking adventure - Hunt, Roderick; Brychta, Alex (Oxford University Press, 1990)
Part of a series designed to teach young children to read English, this series of "Magpie" books carries on from the "Owls" series at Stage 7. There is an extra line of text per page, the sentence structure is more complicated, and many new words are introduced, supported by illustrations.